Analisis Kesiapsiagaan Manajemen Bencana Rumah Sakit TK III Dr R Soeharsono Banjarmasin - Ernawati; Sri Purwanti Ariani; Tri Mawarni; Baidah (Journal of Mandalika Literature, 2024)
Banjarmasin is one of the cities with a high risk of various natural disasters. This is due to its geographical location and environmental conditions that make it vulnerable to flooding and extreme weather changes. Given these potential risks, hospitals operating in Banjarmasin must have strong disaster management preparedness to face various possible disasters. Adequate preparedness is essential to minimize the negative impacts on healthcare services as well as the safety of patients and hospital staff This study aims to analyze the disaster management preparedness of hospitals in Banjarmasin. A descriptive observational study approach was used to obtain an accurate picture of their preparedness. Additionally, a semi-quantitative method was employed to measure and evaluate various aspects of preparedness in a more detailed and structured manner. The primary data for this study were collected through in-depth interviews with hospital experts. These interviews were conducted using a modified version of the Safe Hospital Checklist, which focuses on disaster management, risk management, and preparedness. The results from these interviews will be used to provide recommendations to help hospitals improve their disaster management preparedness